2015
DOI: 10.1186/s12889-015-2155-x
|View full text |Cite
|
Sign up to set email alerts
|

Partner HIV serostatus disclosure and determinants of serodiscordance among prevention of mother to child transmission clients in Nigeria

Abstract: BackgroundSerodiscordance exists when the known HIV result of one member of a couple pair is positive while that of his/her partner is negative. In sub-Saharan Africa, in stable long-term couple partnerships (married or cohabiting), serodiscordance is a growing source of HIV-transmissions. This study aimed to ascertain across Nigeria, serodiscordance prevalence, partner HIV status disclosure and explore associations between suspected determinants and serodiscordance among PMTCT enrolled HIV positive pregnant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Among our cascade groups, newly-diagnosed and ANC women were less likely to know their partner's status, compared to postpartum and LTFU women, and this difference was statistically significant. Previous Nigerian studies reported a similar serodiscordance rate for North-Central Nigeria of 51.9% [ 23 ] and lower rate of 38.5% for South-East Nigeria [ 45 ]. Proportions of HIV-positive women with unknown male partner status of 62.4% and 85% have been reported from studies in North-Central and South-East Nigeria, respectively [ 24 , 45 ], which are much higher than for our study.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Among our cascade groups, newly-diagnosed and ANC women were less likely to know their partner's status, compared to postpartum and LTFU women, and this difference was statistically significant. Previous Nigerian studies reported a similar serodiscordance rate for North-Central Nigeria of 51.9% [ 23 ] and lower rate of 38.5% for South-East Nigeria [ 45 ]. Proportions of HIV-positive women with unknown male partner status of 62.4% and 85% have been reported from studies in North-Central and South-East Nigeria, respectively [ 24 , 45 ], which are much higher than for our study.…”
Section: Discussionmentioning
confidence: 71%
“…Since we could not establish time of HIV diagnosis for our cascade groups, it is not possible to determine how and if this played a role in the observed differences in serodiscordance, and knowledge of partner status. For serodiscordant couples, early partner testing, notification and treatment can avert seroconversion in the HIV-negative partner [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also observed in the present study, that more than one third of those not disclosed, indicated their willingness to disclose now and of those not willing to disclose now, close to three quarters were willing to disclose in the future. This observed willingness of the respondents, does not necessarily translate to disclosure, as reported in a Nigerian study [37], where there was no association between the study participants willingness to disclose and their partners getting tested in spite of the fact that, most of the participants who tested positive to HIV indicated their willingness to disclose.…”
Section: *Significantmentioning
confidence: 61%
“…There is ample data on the impact of expert mothers and similar peer support on PMTCT outcomes, disclosure rates, and experiences among WLHIV in general [2][3][4][5][6][7][21][22][23][24][25]. However, there is little data on disclosure among expert mothers functioning as mentors for other WLHIV.…”
Section: Plos Onementioning
confidence: 99%